2019
DOI: 10.1051/e3sconf/201913001021
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coconut Shell Powder as Functional Filler in Polypropylene during Compounding and Subsequent Molding

Abstract: Fine powder produced from coconut shells (CSP) has been found to be excellent functional filler in polypropylene, significantly increasing flexural and tensile moduli, slightly increasing tensile strength, and good retention of Izod impact strength at weight percentages less than 20 %. The research presented in this paper explores the temperature processing window for coconut shell powder filled polypropylene and the change in the rheological behavior of the polypropylene due to the addition of CSP as function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The review investigates the development of polymer composites reinforced with coconut shell fibers, encompassing manufacturing processes, methodology, and the assessment of mechanical properties and thermal analysis, as well as potential applications (Udhayasankar & Karthikeyan, 2015). Coconut shell powder offers the advantage of higher thermal degradation temperatures due to its high lignin content compared to most other natural fillers (Kirby et al, 2019). Figure 6…”
Section: Modification Coconut Shell Grinding Machinementioning
confidence: 99%
“…The review investigates the development of polymer composites reinforced with coconut shell fibers, encompassing manufacturing processes, methodology, and the assessment of mechanical properties and thermal analysis, as well as potential applications (Udhayasankar & Karthikeyan, 2015). Coconut shell powder offers the advantage of higher thermal degradation temperatures due to its high lignin content compared to most other natural fillers (Kirby et al, 2019). Figure 6…”
Section: Modification Coconut Shell Grinding Machinementioning
confidence: 99%
“…The CS composite sample outperforms the other composite in terms of wear resistance. The sclerenchyma is made up of various cell types, one of which is the sclerid [37].…”
Section: Wear Testmentioning
confidence: 99%
“…Coconuts have sclereids, which are responsible for the stony hardness of their shells. Lignin is thought to act as a cell wall reinforcing agent, polymerizing within cell walls to stiffen them and prevent buckling under mechanical stress [37]. CS is a lignin-rich biomass that is four times harder than hard maple and other hardwoods [33].…”
Section: Wear Testmentioning
confidence: 99%
“…They reported that the ultimate strength and modulus of elasticity of composites decreased as the compositions of coconut shells were increased [16]. There were a number of other studies on coconut shell composites [17][18][19][20][21][22]. However, the compositions of fillers for most biocomposites were below 50% and micrometre of filler sizes.…”
Section: Introductionmentioning
confidence: 99%